2018
DOI: 10.1371/journal.pone.0201886
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing during pregnancy for prevention of mother-to-child transmission of HIV in Ethiopia

Abstract: IntroductionHIV testing during pregnancy provides an entry point to prevention of mother-to-child transmission of HIV and to access treatment for HIV positive women. The study aimed to assess the uptake of HIV testing during pregnancy and associated factors among Ethiopian women.MethodsWe analyzed the 2016 Ethiopian Demographic and Health Survey dataset. Women who gave birth within one year prior to the survey were included in the analysis. Uptake of HIV testing during pregnancy is defined as receiving HIV tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 22 publications
9
52
4
Order By: Relevance
“…In Ethiopia, a nationally-representative study found that 33.7% of the sample population received early ANC visits [3]. Regarding HIV tests during pregnancy, Ejigu et al showed that in Ethiopia, more than 35% of the sample population were tested for HIV [25], which is quite low compared with 75.4% in the present study. This is understandable based on the fact that Ethiopia (2.4%) also has a far lower HIV rate compared with Mozambique (13.2% as of 2015) [26].…”
Section: Discussioncontrasting
confidence: 62%
“…In Ethiopia, a nationally-representative study found that 33.7% of the sample population received early ANC visits [3]. Regarding HIV tests during pregnancy, Ejigu et al showed that in Ethiopia, more than 35% of the sample population were tested for HIV [25], which is quite low compared with 75.4% in the present study. This is understandable based on the fact that Ethiopia (2.4%) also has a far lower HIV rate compared with Mozambique (13.2% as of 2015) [26].…”
Section: Discussioncontrasting
confidence: 62%
“…In this study, pregnant women with a primary and secondary level of education were less likely to accept testing than those with a diploma and above education level, which was in line with a study done in Ethiopia, Congo. [24][25][26] However, this was in contrast with a finding of the study done in Northwest part of Ethiopia; in Gondar and Botswana more pregnant women with no education accepted HIV testing than women with basic education. The possible explanation is that education plays a key role in individual health-seeking behavior, and prevention of mother to child transmission, that promotes human immune virus testing.…”
Section: Discussioncontrasting
confidence: 82%
“…A positive association was observed between awareness of mother to child transmission, and acceptability of HIV testing, which was in line with a previous study done in Ethiopia. 26 Pregnant women with previous knowledge of prevention of mother to child transmission were more likely to accept human immune virus testing than their counterparts, similar to studies done in different parts of Ethiopia. 16,23 This could be due to the higher perceived benefit of human immune virus testing among women who had a better knowledge of mother to child transmission, and prevention of mother to child transmission which in turn influences testing acceptance positively.…”
Section: Discussionsupporting
confidence: 54%
“…Regarding HIV tests during pregnancy, a more recent Ethiopian study found that 35.10% of the sample population were tested for HIV compared with 65.4% in the present study [21]. However, the prevalence of Gambian women taking HIV tests during pregnancy is lower compared with Uganda (81.50%) and Mozambique (69.40%) [22]. In the multivariable analysis, significant sociodemographic differences were observed in the likelihood of the utilization of the ANC services.…”
Section: Discussioncontrasting
confidence: 63%